Non isothermal kinetic study of the aluminium titanate formation in alumina-titania mixtures - Rendtorff,N. M. (2014)
Aluminum titanate (Al2TiO5) is a high refractoriness material with excellent thermal shock resistance. Hence it is suitable for several applications at elevated temperatures where insulation and thermal shock resistance are required. Such as components of internal combustion engines, exhaust port liners, metallurgy, and thermal barriers. The thermal instability of Al2TiO5 at high temperature is another characteristic of this material that has been studied and controlled by the incorporation of several additives. The Al2TiO5 formation from pure oxides presents an endothermic peak in the differential thermal analysis (DTA). The thermodynamic temperature is 1280 ºC. But experimentally, as in every other DTA experiment, these peaks strongly depend on the heating rate: this fact has been extensively employed for the kinetic study of transformation processes and the mechanism determination of chemical reactions. Both activation energies (Ea) and nucleation rates can be obtained from these experiments. The present work reports the formation Ea of Al2TiO5 prepared from pure oxides at air atmosphere by the Kissinger DTA based methods. Previously the particle size distribution of the starting powders together with X-ray diffraction analysis of the starting powders and the resulting materials was carried out. The properties of the Al2TiO5 formation were grouped into two groups corresponding to the low and high heating rates, below and over 5 K/min. Ea values were obtained after the Avrami (n) constant evidenced that the crystallization mechanism is strongly related to the heating rate, even in the wide range studied which includes the technological ones(0.5-40 K/min).